Efektivitas Program Pemberian Makanan Tambahan dalam Meningkatkan Status Gizi Balita Stunting di Wilayah Kerja UPTD Puskesmas Tanjung Selor - Tanty Herlina Sari Tanty; Retha Hani Agustine; Liska Pramudita Pratiwi; Simonalisa Simonalisa; Feranitha Feranitha; Maria Kire Kobun; Basir Basir (Universitas Sumatera Barat, 2026)
Stunting is a chronic nutritional problem in toddlers that remains a national health concern in Indonesia. This study aims to evaluate the effectiveness of the Supplementary Feeding Program (PMT) on improving the nutritional status of stunted toddlers in working area of ​​the UPTD Tanjung Selor Health Center. The research method used a descriptive-analytical qualitative approach by analyzing secondary data from the working area of ​​the UPTD Tanjung Selor Health Center for the period September-October 2024 involving 83 stunted toddlers. The data collected included toddler anthropometric measurements (body weight and height/length) at initial examination and stage V monitoring, toddler identity data, and health complaint records. The results showed an average increase in body weight of 0.39 kg (from 9.34 kg to 9.73 kg) and height/length of 0.74 cm (from 82.15 cm to 82.89 cm). A total of 85.5% of toddlers experienced weight gain, 6.0% experienced weight loss, and 8.4% had incomplete data. No health complaints were found during the monitoring period. The dual intervention approach through nutritional education for parents and direct supplementary feeding proved effective in supporting catch-up growth in stunted toddlers. This program demonstrates that comprehensive and structured nutritional interventions can have a significant positive impact on improving the nutritional status of stunted toddlers.